The role of the sharia supervisory board in the relationship of third-party fund and profits - Fajria Zakiyah; Prayogo Prasojoharto; Sepky Mardian (Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
Purpose - This study aims to find empirical evidence of the effect of growth of Third-Party Funds (TPF) on profit growth with the role of the Sharia Supervisory Board (SSB) as moderator in Islamic banks in Indonesia.Method - This research is an associative research with a quantitative approach that used Panel Data Regression and Moderated Regression Analysis (MRA) as the data analysis methods. The research sample was 58 annual financial reports from 14 Islamic Commercial Banks in Indonesia.Result - TPF had a significant positive effect on bank profit growth, but the role of the SSB could not moderate the growth of TPF on the profit growth of Islamic banks.Implication - The implications of this research can strengthen the belief that Islamic banks need to improve the quality of their services and products to maintain the trust of customers and prospective customers to place their funds in Islamic banks.Originality - The difference in this study when compared to other studies is the role of the Sharia Supervisory Board which is positioned as a moderating variable for the growth of Third-Party Funds on profit growth.